2022
DOI: 10.3390/ijms232314799
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Composition in Diverticular Disease: Implications for Therapy

Abstract: Gut microbiota (GM) composition and its imbalance are crucial in the pathogenesis of several diseases, mainly those affecting the gastrointestinal tract. Colon diverticulosis and its clinical manifestations (diverticular disease, DD) are among the most common digestive disorders in developed countries. In recent literature, the role of GM imbalance in the onset of the different manifestations within the clinical spectrum of DD has been highlighted. This narrative review aims to summarize and critically analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…compared with 35 controls without any diverticula 107 . This suggests a potential role of microbiota in the development of symptoms, and the symbiotic and pathognomonic role of the gut microbiome requires further study 108 ( Table 3 lists intrinsic factors related to DD).…”
Section: Geneticsmentioning
confidence: 99%
“…compared with 35 controls without any diverticula 107 . This suggests a potential role of microbiota in the development of symptoms, and the symbiotic and pathognomonic role of the gut microbiome requires further study 108 ( Table 3 lists intrinsic factors related to DD).…”
Section: Geneticsmentioning
confidence: 99%
“… 45 Other studies showed that different microbiota compositions were associated with SUDD. 50 Therefore, colonic microbiota has been considered a therapeutic target for probiotics, fibers, and non-absorbable antibiotics.…”
Section: Symptomatic Uncomplicated Diverticular Diseasementioning
confidence: 99%